Haglund's Syndrome: endoscopic or open treatment? - Lughi, Marcello (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work. With the term “Haglund›s syndrome” we define a conditioncharacterized clinically by pain at the insertion of Achille›s tendon and, anatomopathologically, due to thepresence of retrocalcaneal bursitis and at times associated with an insertional Achille›s tendinopathy. Theaim of the work is to correlate the most reliable and reproducible treatment possible to the aforementionedvariables of Haglund›s syndrome. Methods. The classic syndromic picture is characterized by pain caused byretrocalcaneal bursitis. In some cases, symptoms of insertional tendinopathy are associated with bursitis pain.In those frameworks where symptoms were mainly exacerbated by the bursitis inflammation we have used anendoscopic technique for the resection of the underlying bone deformation and the bursa. An open technique,described in the literature as bridge sutures, was used for those patients with tendinopathic problems. Whilea homologous PRP unit was infiltrated in patients with degenerative insertional tendinopathy. Results.The group of patients that participated to the study was heterogeneous in age and functional requirementstherefore presenting different anatomopathological characteristics. For these reasons considerations withcorrect statistical meaning are not possible. Despite different post-operative programs, patients demonstratedoptimal clinical and functional recovery. There were no local neurological or skin complications. Conclusions.Haglund›s syndrome can have different clinical and anatomopathological patterns where conservativetreatment is unsuccessful surgical solutions must be adopted. The latter have shown to be reliable andreproducible with a very low rate of complications. (www.actabiomedica.it)